Do parapatric populations of the ticks Amblyomma tonelliae Nava, Beati & Labruna, 2014 and Amblyomma sculptum Berlese, 1888 (Acari: Ixodidae) hybridize? - Tarragona, Evelina Luisa; Lado, Paula; Beati, Lorenza; Mangold, Atilio Jose; Guglielmone, Alberto; Nava, Santiago (Royal Entomological Society, 2023)
This work aimed to determine if the tick species, Amblyomma sculptum and Amblyomma tonelliae, hybridize along their contact zones in Argentina. Free-living adults and nymphs of A. sculptum and A. tonelliae were collected in seven sampling locations of northern Argentina. In four of them, the two species occur in parapatry (possible hybrid zone) whereas in the other three sites, only one species is known to occur. A total of 65 A. sculptum and 65 A. tonelliae from both, allopatric and parapatric populations, were analysed. The nuclear (ITS2) and mitochondrial (COI and 12SrDNA) gene sequences of each tick were amplified and analysed to verify whether or not they could reveal the presence of hybrids among the parapatric samples. No morphological and molecular evidence was found to support the hypothesis of ongoing natural hybridization. Intrinsic postzygotic barriers may be the cause of lack of gene flow between the two species in areas of co-ocurrence. The results can be explained by the length of time the two lineages spent in allopatry since the middle of the Miocene and before their respective distribution range expanded again reaching a narrow secondary contact zone.